촉매를 재생하는 방법 및 알칸 및/또는 알킬 방향족 탄화수소를 업그레이드하는 방법 - BAO XIAOYING (2024)
본 발명은, 10족 원소, 무기 지지체 및 오염물질을 포함할 수 있는 적어도 부분적으로 비활성화된 촉매를 재생하는 방법에 관한 것이다. 상기 10족 원소는 무기 지지체의 중량을 기준으로 0.06 중량% 내지 6 중량%의 농도를 가질 수 있다. 상기 방법은, (I) 가열 가스 혼합물의 총 몰수를 기준으로 5 몰% 초과의 농도로 H2O를 포함할 수 있는 가열 가스 혼합물을 사용하여 상기 비활성화된 촉매를 가열하여 전구체 촉매를 생성하는 단계를 포함한다. 상기 방법은 또한, (II) 산화성 가스의 총 몰수를 기준으로 5 몰% 이하의 H2O를 포함할 수 있는 산화성 가스를 제공하는 단계, 및 (III) 산화 온도에서 상기 전구체 촉매를 적어도 30초 동안 상기 산화성 가스와 접촉시켜 산화된 전구체 촉매를 생성하는 단계를 포함한다. 상기 방법은 또한, (IV) 상기 산화된 전구체 촉매로부터 재생된 촉매를 얻는 단계를 포함할 수 있다. Processes for regenerating an at least partially deactivated catalyst that can include a Group (10) element, an inorganic support, and a contaminant. The Group (10) element can have a concentration of from 0.06 wt % to 6 wt %, based on the weight of the inorganic support. The process can include (I) heating the deactivated catalyst using a heating gas mixture that includes H2O at a concentration >5 mol %, based on the total moles in the mixture to produce a precursor catalyst. The process can also include (II) providing an oxidative gas that includes ≤5 mol % of H2O, based on the total moles in the oxidative gas, and (III) contacting the precursor catalyst at an oxidizing temperature with the oxidative gas for a duration of at least 30 seconds to produce an oxidized precursor catalyst. The process can also include (IV) obtaining a regenerated catalyst from the oxidized precursor catalyst.